Shaping children's healthy eating habits with food placements? Food placements of high and low nutritional value in cartoons, Children's BMI, food-related parental mediation strategies, and food choice. (1st January 2018) - Naderer, Brigitte; Matthes, Jörg; Binder, Alice; Marquart, Franziska; Mayrhofer, Mira; Obereder, Agnes; Spielvogel, Ines
Abstract: Research on media induced food choices of children has not sufficiently investigated whether food placements of snacks high in nutritional value can strengthen children's healthy eating behavior. Furthermore, we lack knowledge about the moderating role of children's individual characteristics such as parental food-related mediation or BMI. The current study combines data from an experiment involving children with a survey of their parents. We exposed children to a cartoon either containing no food placements, placements of mandarins (i.e., snack high in nutritional value), or placements of fruit gums (i.e., snack low in nutritional value). Afterwards, food consumption was measured by giving children the option to choose between fruit gums or mandarins. Children in both snack placement conditions showed stronger preference for the snack low in nutritional value (i.e., fruit gum) compared to the control group. Interestingly, neither restrictive nor active food-related mediation prevented the effects of the placements on children's choice of snacks low in nutritional value. Compared to children with a low BMI, children with high BMI levels had a stronger disposition to choose the fruit gums if a snack high in nutritional value (i.e., mandarin) was presented. Thus, making snacks high in nutritional attractive for children through media presentation might need stronger persuasive cues.